Who Deserves Access to Care in Children's Hospitals?. Issue 6 (26th December 2018) - Caruso Brown, Amy E.; Frega, Katherine
Abstract: An eighteen‐year‐old with sickle cell disease was admitted to the pediatric hematology service at his local children's hospital for management of an acute pain crisis, one of many such admissions. He had a good relationship with his primary hematologist and primary nurse, but with other health care providers, there was evident friction. Sometimes, he was simply rude, rolling over and pretending to sleep in response to questions about his symptoms. When frustrated or convinced that his pain was not being addressed appropriately, he was prone to yelling and cursing at his nurses. After members of the health care team complained, their supervisor decided to transfer the patient to an adult general medicine service. Reasons cited for the transition included the stressful work environment created by the patient's actions, his refusal to follow directives from staff (although he was generally adherent to treatment), and the hypothetical harm to other young patients who might witness his behavior. Was this a just outcome? Is it ever permissible to deny access to pediatric care to a patient whose best interests would be served by it? Can access be withheld for "bad" behavior, and can transfer of care be wielded as a punishment?